Assessment of Brain-Derived Neurotrophic Factor on Retinal Structure and Visual Function in Rodent Models of Optic Nerve Crush - Takazumi Taniguchi; Najam A. Sharif; Takashi Ota; Rafal A. Farjo; Rebecca Rausch (MDPI AG, 2024)
The effects of brain-derived neurotrophic factor (BDNF) on retinal ganglion cell (RGC) survival and visual function were assessed in rat and mouse models of optic nerve (ON) crush. ONs were crushed on Day 1, followed by intravitreal injections of a vehicle or BDNF on Days 1 and 8. The spatial frequency threshold was measured using optokinetic tracking on Days 7 and 14. On Day 15, ganglion cell complex (GCC) thickness was quantified using optical coherence tomography. Furthermore, all eyes were enucleated for immunohistochemical analysis of the surviving RGC somas and axons. BDNF significantly reduced the RGC soma in mice and increased GCC thickness in intact eyes, with apparent axonal swelling in both species. It displayed significantly greater RGC soma survival in eyes with ON injury, with moderately thicker axonal bundles in both species and a thicker GCC in rats. Visual function was significantly reduced in all ON-crushed animals, regardless of BDNF treatment. Thus, we obtained a comprehensive analysis of the structural and functional impact of BDNF in intact and ON-crushed eyes in two rodent models. Our results provide a foundation for further BDNF evaluation and the design of preclinical studies on neuroprotectants using BDNF as a reference positive control.